Grêmio estudantil e participação do estudante - Carlos, Aparecida da Graça (2006)
The present dissertation aims to investigate the opinion of the Grêmio Estudantil leaders about their participation in this school association as well to know what they think about the main purpose of this association at school and also to discuss the relationship between these leadears and their classmates, the teaching staff, the headmaster and all the other people who work at the school. A list of questions to be individually answered allowed me to collect statistics and at the same time to deal with scale of attitude tests. The questionnaire was got in four public schools of the state of São Paulo and collected information not only about the family of the Grêmio Estudantil leaders but also about the finality of this school association among the students. The answers were analysed according to the society critic theory, written by Adorno and Marcuse. The analyses showed that the efficacy of the institutionalization has contributed to a gradual decrease in the maintenance of different dialogues at school and has weakened, on the other hand, the critical potential of the students, what restrict the participation of members of the Grêmio Estudantil to activities that involve sociability , leisure and requests of repairs in the school building